Multimodal Analysis as a Way to Operationalise Objectivity in Audio Description: A Corpus-based Study of Spanish Series on Netflix - Romero Muñoz, Alejandro (Journal of Audiovisual Translation, 2023)
Objectivity is a constant recommendation in audio description (AD) guidelines. However, some scholars have pointed to the advantages of a more subjective, creative, or narrative rendition. In this paper, we seek to determine to what extent subjectivity and objectivity coexist in Spanish filmic AD. In order to fulfil our aim, we operationalised objectivity by means of multimodal analysis based on Chaume’s (2004) classification of meaning codes. To operationalise objectivity through multimodality, we employed a qualitative content analysis and examined whether visual and acoustic information was rendered objectively or subjectively in a corpus of four Spanish AD scripts from Netflix. Our results show, firstly, that objectivity and subjectivity interact in the mobility, iconographic, and editing codes. Moreover, dissimilarities arise in the way these meaning codes are described in Spanish: movement is mainly described objectively, whereas iconography and editing are rendered either subjectively or objectively. In conclusion, we can state that neither is objectivity systematically applied in our AD scripts, nor is a purely narrative AD to be found, but rather a mixture of both coexists. Furthermore, this coexistence seems unequal, since different tendencies can be identified in the way that movement, editing, and iconography are described. Lay summary Audio description is an oral narration aimed at blind people that provides information about what is going on in an audiovisual product. The traditional view has been to inform objectively about the audio description contents, but some scholars support more subjective or creative alternatives. This papers seeks to observe whether audio description actually contains both subjective and objective elements. In order to find these elements, we used multimodality, a kind of analysis that shows how visual and acoustic information interact to create meaning. In this analysis we exposed instances of objective and subjective elements in a group of Spanish audio descriptions from Netflix. Our results show that there are objective and subjective elements when informing about movement, symbols, or spatio-temporal changes. However, these elements are not balanced, since movement is mainly described objectively, whereas symbols and spatio-temporal changes are described either subjectively or objectively. In conclusion, we can state that current audio description seems to be the result of a mixture of subjective and objective elements.